Gender and the environmental health agenda: A qualitative study of policy, academic, and advocacy perspectives in Peru - Laura J. Brown; Billie M. Turner; Victoria Cavero; Elaine C. Flores (Elsevier, 2023)
Introduction: Women, especially those living in low-and-middle-income countries experience increased exposure to and impacts of environmental threats. Peru is especially susceptible, with high levels of pollutants associated with extractive industries, and climatic-related disasters exacerbated by climate change. International policies and movements are increasingly calling for a gendered approach to environmental health. We aimed to understand the current Peruvian research, advocacy, and policy landscape at the environment-gender-health nexus. Methods: We held 18 in-depth semi-structured interviews with key informants from the Peruvian Government, academia, and non-governmental organizations to explore how a gender-sensitive approach and interdisciplinary environmental health collaborations are delivered. We used thematic analysis to compare gender approaches, priorities, and barriers/facilitators to delivering projects within this nexus. Results: We remotely interviewed 6 representatives of each sector between July 2020 and March 2021. Interviewees mentioned the detrimental role of weak institutions, multilevel corruption, and the lack of interdisciplinarity and intersectorality across environmental health programs and research. They described several barriers to successful collaboration across organizations and sectors, including funding scandals related to extractive economies, high staff turnover impairing long-term program implementation, and machismo culture in organizations and communities. Women's empowerment was described as important for successful program delivery, especially in female-led associations. Some interviewees emphasized the invisibilization of vulnerable groups, such as girls, teenagers, pregnant women, victims of gender-based violence, and LGBTQI+ people. Conclusions: These qualitative findings highlight the multiple and inter-related contextual issues faced by environmentally threatened communities in Peru, and how macrostructural barriers contribute to a paucity of sustainable, gender-oriented, environmental health projects.